FUZZY CHOQUET INTEGRAL APPROACH FOR MULTI CRITERIA SUPPLIER EVALUATION PROBLEM - Ayyildiz, Gokhan; Cetin Demirel, Nihan (YILDIZ TECHNICAL UNIV, 2010)
During the supplier selection evaluation, many factors like tangible, intangible, financial and non-financial etc. must be considered. In literature, many multi criteria decision making (MCDM) methods have been used for supplier selection problems. Exposing a different strategy in supplier selection and using the Generalized Choquet Fuzzy Integral (GCFI) algorithm with the proposed supplier evaluation model in which the dependent criteria are evaluated, more effective results are obtained. The effect of dependent criteria over an alternative selection is taken into account. It is obtained that a firm in textile sector has determined the best alternative out of its suppliers.
Keywords: Supplier evaluation; generalized choquet fuzzy integral; multi criteria decision making; Engineering